Original article Expression of 8-oxoguanine DNA glycosylase 1 (OGG1) and the level of p53 and TNF-αlpha proteins in peripheral lymphocytes of patients with Alzheimer’s disease - Dezor, Mateusz; Dorszewska, Jolanta; Florczak, Jolanta; Kempisty, Bartosz; Jaroszewska-Kolecka, Joanna; Rozycka, Agata; Polrolniczak, Anna; Bugaj, Robert; Jagodzinski, Pawel P.; Kozubski, Wojciech (Folia Neuropathologica, 2011)
The aim of the study was to determine the extent of oxidative DNA damage (levels of 8-oxo2dG) and expression of OGG1 and p53 and TNF- proteins in lymphocytes of Alzheimer’s disease (AD) patients and a control group. The studies were conducted on 41 patients with AD, including 25 women and 16 men aged 34-84 years. The control group included 51 individuals, 20 women and 31 men aged 22-83 years. The level of 8-oxo2dG was determined using HPLC/EC/UV, and the level of OGG1 and p53 and TNF- proteins was determined with the Western blot method. The results showed that both proteins participating in DNA repair (OGG1, p53) and the inflammatory protein TNF- are involved in pathogenesis of neurodegenerative diseases. It also seems that a specific system for DNA repair (OGG1) may contribute to downregulation of the inflammatory factor (TNF-) level, especially in the early stages of dementia. Moreover, the results showed that p53 protein can fulfil its function in DNA damage repair only in early stages of dementia. It is possible that OGG1 and p53 and TNF- proteins together or separately may be involved in pathogenesis of AD by repair of oxidative DNA damage and/or apoptosis.